INHIBITION TEST OF METHANOL EXTRACT FROM SOURSOP LEAF (Annona muricata Linn.) AGAINST Streptococcus mutans BACTERIA* - Raudhatul Jannah; Muhammad Ali Husni; Risa Nursanty (Universitas Syiah Kuala, 2017)
Abstract. Dental caries is a disease with a high prevalence of caries in Indonesia is caused by the bacterium Streptococcus mutans. The leaves of the soursop (Annona muricata Linn.) is one of the herbs that can remove dental plaque. This study aims to determine the chemical content and measure the inhibitory antibacterial soursop leaft methanol extractin inhibiting the growth of Streptococcus mutans bacteria. Phytochemical screening stated that the leaf of the soursop contains flavonoids, alkaloids, tannins, steroids, glycosides and saponins. Test of inhibition were measured using paper disc diffusion method with variation concentrations of 5, 10, 15 20, and 25%, positive control is tetrasilkin 30 µg, and a negative control is methanol. Antibacterial test results showed that the methanol extract of soursop leaves have antibacterial activity against Streptococcus mutans at concentrations of 5, 10, 15, 20 and 25% with inhibitory diameter of 9,1; 10,57; 11,53; 12,01 and 13,75 mm respectively. Keywords: Soursop leaves, Dental caries, Streptococcus mutans, Methanol.*Judul ini telah dipresentasikan pada Seminar Nasional: Indonesian Students Conference on Science and Mathematics (ISCSM) 11-12 November 2015, Banda Aceh Indonesia